Second-step lectotypification of three names of Araceae from India - Manudev, K.m.; Nampy, Santhosh (Phytotaxa, 2017)
During a taxonomic revision of the genus Arisaema (Araceae) in India, three names, i.e. Arisaema echinatum, A. leschenaultii and A. nepenthoides were found to lack a proper typification. The erroneous lectotypifications are rectified by selecting lectotypes.